Islamic Boarding Schools and Community ‎Entrepreneurship: a New Model Of Islamic ‎Education Based on Entrepreneurship In ‎Indonesia - Ghafar, Muhammad (TADRIS: Jurnal Pendidikan Islam, 2023)
This article analyzes and discovers the educational model of Darul Amien Banyuwangi Islamic boarding school based on entrepreneurship. This type of research is field research; the data sources in this study were obtained from clerics, administrators, and students involved in entrepreneurial activities. They collect data using in-depth interview techniques, non-participant observation, and documentation. Testing the validity of the data in this study was conducted by testing its credibility. The results of the study found three models of entrepreneurship-based Islamic boarding school education, namely firstly, instilling a sense of responsibility, independence, and kinship in the togetherness of students, secondly the introduction of business units owned by Islamic boarding schools and empowering student apprentices through on the job training, thirdly coaching through mentoring of field experts. Businessman. Through these three stages, it is hoped that Islamic boarding schools will also give birth to independent entrepreneurship in Indonesia.